Styrenic resin composition
Patent Information
- Application Number
- JP2020101699
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-06-11
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2040-06-11
AI Technical Summary
【0011】 本発明の樹脂組成物は、耐薬品性、耐熱性及び耐衝撃性に優れたものである。したがって本発明の樹脂組成物はOA機器、家電製品、食器、包装容器等の用途で有効に利用できる。
Smart Images

Figure 0007640233000004 
Figure 0007640233000005 
Figure 0007640233000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a resin composition having excellent chemical resistance, heat resistance and impact resistance. [Background technology]
[0002] Taking advantage of their properties, styrene resins are used in a wide range of fields, including office equipment such as personal computers, printers, and copiers, and home appliances such as TVs and audio equipment.
[0003] On the other hand, polyester resins are excellent in mechanical properties and are therefore widely used in various industrial applications such as films, sheets, tableware, and packaging containers.
[0004] In recent years, there has been a demand for reducing carbon dioxide emissions due to the problem of global warming, and polylactic acid has attracted attention as one of the "carbon-neutral" polyester resins that apparently do not emit carbon dioxide. However, although polylactic acid has excellent chemical resistance, it is poor in heat resistance and impact resistance, and polymer alloys with styrene-based resins and the like have been considered in recent years.
[0005] As a method for improving heat resistance, a method of adding a styrene-based resin consisting of a copolymer of an aromatic vinyl monomer and an unsaturated carboxylic acid compound to a styrene-based resin / polylactic acid has been exemplified. Although this method improves heat resistance, it has the problem of insufficient impact resistance (Patent Document 1).
[0006] As a method for improving impact resistance, a method of adding a copolymer of butadiene and an ethylenically unsaturated carboxylic acid ester to a styrene-based resin / polylactic acid has been exemplified. However, although this method improves impact resistance, it has the problem of deteriorating heat resistance (Patent Document 2). [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2008-050427 A [Patent Document 2] JP 2016-199654 A Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a resin composition having excellent chemical resistance, heat resistance and impact resistance. [Means for solving the problem]
[0009] Means for Solving These Problems The present inventors have conducted intensive research to find a solution to these problems, and as a result have discovered that a resin composition obtained by adding a polymer containing a structural unit having a carboxyl group to a styrene-based resin, a polyester-based resin, and an acrylic-based resin can provide a resin composition having excellent chemical resistance, heat resistance, and impact resistance, thereby arriving at the present invention.
[0010] That is, the present invention is as follows. (1) A styrene-based resin composition comprising 30 to 80 parts by mass of a styrene-based resin (A), 20 to 70 parts by mass of a polyester-based resin (B), an acrylic resin (C), and a polymer (D), The total amount of the styrene-based resin (A) and the polyester-based resin (B) is 100 parts by mass, The content of the acrylic resin (C) is 0.1 parts by mass to 10 parts by mass per 100 parts by mass of the total of the styrene resin (A) and the polyester resin (B), The content of the polymer (D) is 1 part by mass to 35 parts by mass per 100 parts by mass of the total of the styrene-based resin (A) and the polyester-based resin (B), The polymer (D) is a styrene-(meth)acrylic acid copolymer, The styrene resin (A) is a rubber-modified polystyrene. the law of nature, The main constituent unit of the acrylic resin (C) is a (meth)acrylate unit. Styrenic resin composition. (2) The styrene-based resin composition according to (1), wherein the polyester-based resin (B) is polylactic acid. (3) The styrene-based resin composition according to (1) or (2), wherein the acrylic resin (C) has a weight-average molecular weight of 1.5 million to 6 million. (4) Structural unit of acrylic resin (C) teeth Methyl methacrylate unit The main component isThe styrene-based resin composition according to any one of (1) to (3), wherein the content of the styrene-based resin is 60 mass % or more. (5) The styrene-based resin composition according to any one of (1) to (4), wherein the content of the structural unit having a carboxyl group in the polymer (D) is 0.5 to 9.5% by mass. (6) A sheet comprising at least one resin composition layer containing, as a main component, the styrene-based resin composition according to any one of (1) to (5). (7) A food packaging container formed from the sheet according to (6). Effect of the Invention
[0011] The resin composition of the present invention has excellent chemical resistance, heat resistance and impact resistance, and can therefore be effectively used in applications such as office automation equipment, home appliances, tableware and packaging containers. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a side view of a constant strain chemical resistance test device for evaluating chemical resistance. [Diagram 2] FIG. 2 is a plan view of a constant strain chemical resistance test device for evaluating chemical resistance. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] The resin composition of the present invention will be described in detail below.
[0014] First, the styrene resin (A) will be described. The styrene resin (A) used in the present invention is obtained by polymerizing a monomer of an aromatic vinyl compound. The aromatic vinyl compound monomer may be a known one such as styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, or 2,4-dimethylstyrene, but is preferably styrene. These monomers may be used alone or in combination. In addition, monomers such as acrylonitrile, ethylene, and propylene that are copolymerizable with these monomers may be added and polymerized as long as they do not impair the performance of the styrene resin (A).
[0015] The total volatile matter content (TVM) contained in the (A) styrene-based resin is preferably 500 ppm or less. By keeping it 500 ppm or less, the amount of resin that adheres to the die outlet can be reduced, which is preferable. It is particularly preferable that it is 400 ppm or less.
[0016] The (A) styrene resin may be modified with a conjugated diene rubber polymer as required. Examples of the conjugated diene rubber polymer used for rubber modification include polybutadiene, random or block copolymers of styrene-butadiene, polyisoprene, polychloroprene, random, block or graft copolymers of styrene-isoprene, ethylene-propylene rubber, and ethylene-propylene-diene rubber, with polybutadiene and random, block or graft copolymers of styrene-butadiene being particularly preferred. These may also be partially hydrogenated.
[0017] Examples of such (A) styrene-based resins include polystyrene (GPPS), rubber-modified polystyrene (HIPS), ABS resin (acrylonitrile-butadiene-styrene copolymer), AS resin (acrylonitrile-styrene copolymer), AAS resin (acrylonitrile-acrylic rubber-styrene copolymer), AES resin (acrylonitrile-ethylene propylene-styrene copolymer), etc. Among these, rubber-modified polystyrene is preferred because it can particularly increase the impact resistance of the resin composition.
[0018] The molecular weight of the aromatic vinyl polymer of the rubber-modified polystyrene is not particularly limited, but the reduced viscosity (ηsp / C) is preferably 0.5 to 1.0. A reduced viscosity of 0.5 or more is preferable because the molten strand of the resin is less likely to break, which is advantageous for stable production. Also, a reduced viscosity of 1.0 or less is preferable because the fluidity of the molten resin can be secured.
[0019] The content of the rubber-like polymer in the rubber-modified polystyrene is not particularly limited, but is preferably 3 to 15% by mass. This range of the rubber-like polymer content is preferable because it provides a good balance between the impact resistance and rigidity of the molded product.
[0020] Next, the polyester resin (B) will be described. The polyester resin (B) used in the present invention is a general term for a polymer having an ester bond obtained by polymerizing a monomer containing a carboxylic acid and an alcohol.
[0021] (B) Polyester-based resins can be obtained by polymerization of monomers having dicarboxylic acids and diols as main components. Examples of such polyester-based resins include polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate, polybutylene naphthalate, polyhexamethylene terephthalate, and polyhexamethylene naphthalate, but the present invention is not limited to these.
[0022] Among the monomers of these polyester resins, examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, 4,4'-diphenyldicarboxylic acid, 4,4'-diphenyletherdicarboxylic acid, and 4,4'-diphenylsulfonedicarboxylic acid. Examples of aliphatic dicarboxylic acids include adipic acid, suberic acid, sebacic acid, dimer acid, dodecanedioic acid, cyclohexanedicarboxylic acid, and ester derivatives thereof. These acid components may be used alone or in combination of two or more, and may also be partially copolymerized with oxyacids such as hydroxybenzoic acid.
[0023] Examples of the diol component include ethylene glycol, 1,2-propanediol, 1,3-propanediol, neopentyl glycol, 1,3-butanediol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,2-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, 1,4-cyclohexanedimethanol, diethylene glycol, triethylene glycol, polyalkylene glycol, 2,2-bis(4-hydroxyethoxyphenyl)propane, isosorbate, and spiroglycol.
[0024] On the other hand, the (B) polyester resin can also be obtained by polymerizing a monomer having both a carboxylic acid and an alcohol in a single compound. An example of such a polyester resin is polylactic acid.
[0025] Of these polyester resins (B), polylactic acid is preferred from the viewpoint of carbon neutrality.
[0026] The polylactic acid used is poly(L-lactic acid). From the viewpoint of reducing carbon dioxide emissions, plant-derived raw materials are preferred.
[0027] In the case of poly(L-lactic acid), the crystallization speed varies depending on the ratio of the D-lactic acid component. In consideration of the heat resistance and moldability of the resin composition of the present invention, the ratio of the D-lactic acid component is preferably 0.01 to 5.0 mol %, and more preferably in the range of 0.01 to 1.5 mol %.
[0028] The molecular weight of polylactic acid is preferably in the range of 50,000 to 400,000 in terms of weight average molecular weight Mw, and particularly preferably in the range of 100,000 to 300,000.
[0029] The lactide content of polylactic acid is preferably 0.01 to 0.50 parts by mass per 100 parts by mass of polylactic acid, which is preferable because the amount of resin adhering to the die outlet can be reduced by keeping the lactide content in this range.
[0030] The ratio of (A) styrene resin to (B) polyester resin must be 20 to 70 parts by mass when the total of (A) styrene resin and (B) polyester resin is 100 parts by mass. When the ratio of (B) polyester resin is within this range, chemical resistance, heat resistance, and impact resistance are particularly high.
[0031] Next, the (C) acrylic resin will be described. In the present invention, the (C) acrylic resin refers to a polymer obtained by polymerization of an acrylic monomer, etc. By adding the (C) acrylic resin, it is possible to exert an effect of suppressing the formation of resin deposits, and also to improve chemical resistance and impact resistance.
[0032] The weight-average molecular weight (Mw) of the (C) acrylic resin is preferably 1.5 million to 6 million. When the weight-average molecular weight (Mw) of the acrylic resin is in this range, the effects of reducing resin buildup and improving chemical resistance and impact resistance are particularly exhibited while suppressing gelation during extrusion molding, which is preferable.
[0033] The type of acrylic monomer is not particularly limited as long as it does not impair the effects of the present invention. For example, homopolymers of acrylate monomers such as methyl acrylate, ethyl acrylate, isopropyl acrylate, butyl acrylate, 2-ethylhexyl acrylate, benzyl acrylate, cyclohexyl acrylate, phenyl acrylate, and chloroethyl acrylate, and homopolymers of methacrylate monomers such as methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, butyl methacrylate, 2-ethylhexyl methacrylate, benzyl methacrylate, cyclohexyl methacrylate, phenyl methacrylate, and chloroethyl methacrylate, and copolymers obtained by copolymerizing two or more of these monomers can be used.
[0034] The structural unit of the (C) acrylic resin is mainly composed of methyl methacrylate units, and the content thereof is preferably 60% by mass or more. When the content of the methyl methacrylate units of the acrylic resin is within this range, the resin exhibits a slime suppressing effect and improves chemical resistance and impact resistance. It is particularly preferably 70% by mass or more.
[0035] The content of the (C) acrylic resin is preferably 0.1 to 10 parts by mass per 100 parts by mass of the total of the (A) styrene resin and the (B) polyester resin. By having the (C) acrylic resin content in this range, gelation during extrusion molding is suppressed, while reducing resin buildup and improving chemical resistance and impact resistance.
[0036] The (C) acrylic resin may be one obtained by adding and polymerizing, in addition to these acrylic monomers, vinyl monomers copolymerizable therewith, so long as the effects of the present invention are not impaired. For example, monomers such as α-olefins, unsaturated nitriles, unsaturated carboxylic acid esters, and polyunsaturated compounds such as ethylene glycol di(meth)acrylate may be added.
[0037] Examples of the polymerization method for the (C) acrylic resin include known polymerization methods such as emulsion polymerization, soap-free emulsion polymerization, fine suspension polymerization, suspension polymerization, bulk polymerization, solution polymerization, etc. Among these polymerization methods, emulsion polymerization is preferred because it is easy to produce a high molecular weight substance.
[0038] As the emulsifier for producing the (C) acrylic resin by emulsion polymerization, a known emulsifier can be used, such as an anionic emulsifier, a nonionic emulsifier, a polymer emulsifier, or a reactive emulsifier having a radically polymerizable unsaturated double bond in the molecule.
[0039] The type of the polymer containing a structural unit having a carboxyl group (D) is not particularly limited as long as it does not impair the effects of the present invention, and examples thereof include polyacrylic acid, polymethacrylic acid, styrene-acrylic acid copolymer, and styrene-methacrylic acid copolymer, and these polymers containing a structural unit having a carboxyl group may be in the form of an acid anhydride such as a styrene-maleic anhydride copolymer or a styrene-itaconic anhydride copolymer. Among these, a styrene-(meth)acrylic acid copolymer is preferred because it provides the resin composition with particularly high heat resistance and impact resistance.
[0040] In the polymer (D) of the present invention, the content of the structural unit having a carboxyl group is preferably 0.5 to 9.5 mass%, and more preferably 0.5 to 5 mass%, when the polymer (D) is taken as 100 mass%, because the heat resistance and impact resistance are particularly high. The content of the structural unit having a carboxyl group can be adjusted by the concentration of the structural unit having a carboxyl group in the raw material liquid in the polymerization step.
[0041] The content of the (D) polymer of the present invention is preferably 1 to 35 parts by mass per 100 parts by mass of the total of the (A) styrene-based resin and the (B) polyester-based resin. When the (D) polymer content is within this range, the heat resistance and impact resistance are particularly high.
[0042] Other additives, such as plasticizers, spreading agents, solvents, ultraviolet absorbers, antioxidants, antiaging agents, light stabilizers, stabilizers, antistatic agents, colorants, dyes and pigments, fillers, color inhibitors, reinforcing agents, compatibilizers, crystallization accelerators, flame retardants, flame retardant assistants, and the like, may be added within the scope of the present invention.
[0043] In particular, a copolymer of methyl methacrylate, butadiene, and styrene (MBS) as a reinforcing agent, talc as a crystallization promoter, and liquid paraffin as a spreading agent can be suitably added. MBS is preferred because it has good dispersibility with any of (A) styrene-based resin, (B) polyester-based resin, (C) acrylic resin, and (D) polymers containing structural units having a carboxyl group, and can efficiently reinforce the impact resistance of the resin composition of the present invention. Talc is preferred because it can promote the crystallization of (B) polyester-based resin in the present invention and can improve the heat resistance and mechanical strength of the resin composition. Liquid paraffin is a saturated hydrocarbon refined by removing impurities such as aromatic hydrocarbons and sulfur compounds contained in the lubricating oil fraction of petroleum with sulfuric anhydride or fuming sulfuric acid, and is preferred because it can suppress classification between resins with different specific gravities when mixing the resin composition of the present invention, thereby suppressing quality variation of the resin composition during extrusion production.
[0044] The method of adding these is not particularly limited, and may be a known method. For example, the additives may be added in a raw material charging step, polymerization step, or finishing step during the production of the (A) styrene-based resin or (B) polyester-based resin, or in a step of mixing the resin composition using an extruder or molding machine.
[0045] Next, a method for producing the resin composition of the present invention will be described.
[0046] The method for mixing the resin composition of the present invention is not particularly limited, and known mixing techniques can be applied. For example, a homogeneous resin composition can be produced by mixing various raw materials in advance using a mixing device such as a mixer-type mixer, a V-type blender, or a tumbler-type mixer, and melt-kneading the mixture. The melt-kneading device is also not particularly limited, and examples thereof include a Banbury mixer, a kneader, a roll, a single-screw extruder, a special single-screw extruder, and a twin-screw extruder. In addition, there is also a method in which other additives are added separately from the middle of a melt-kneading device such as an extruder.
[0047] The molding method for obtaining a molded article from the resin composition of the present invention is not particularly limited, and known molding methods such as extrusion molding methods such as calendar molding, blow molding, extrusion foam molding, profile extrusion molding, lamination molding, inflation molding, T-die film molding, sheet molding, vacuum molding, and pressure molding, and injection molding methods such as injection molding, RIM molding, and injection foam molding can be suitably used, with injection molding or sheet molding being preferred. EXAMPLES
[0048] The present invention will be described in detail below with reference to examples and comparative examples, but the present invention is not limited to these.
[0049] The materials used in the examples and comparative examples are as follows. (A-1) Rubber-modified impact-resistant polystyrene resin manufactured by Toyo Styrene Co., Ltd. (reduced viscosity 0.89 dl / g, rubber-like polymer content 6.9 mass%, Charpy impact strength 11 kJ / m2, Vicat softening temperature 92°C) (A-2) Polystyrene resin manufactured by Toyo Styrene Co., Ltd. (reduced viscosity 0.94 dl / g, Charpy impact strength 2.1 kJ / m2, Vicat softening temperature 99°C)
[0050] (B-1) Polyester resin, polylactic acid, Kaisei Seibutsu REVODE190 (Ratio of D-lactic acid component: 0.5 mol%, weight average molecular weight (Mw): 200,000, lactide content: 0.20% by mass) (B-2) Polyester resin PET Eastman PET-G GN001
[0051] (C-1) Manufacturing of acrylic resin Into a separable flask (capacity 5 liters) equipped with a thermometer, a nitrogen inlet tube, a cooling tube and a stirrer, 300 parts by mass (3000 grams) of ion-exchanged water as a dispersion medium, 1.1 parts by mass of sodium dodecylbenzenesulfonate as an emulsifier, 0.009 parts by mass of n-octyl mercaptan as a chain transfer agent, 75 parts by mass of methyl methacrylate as a monomer, and 25 parts by mass of butyl acrylate were added. The atmosphere in the flask was replaced with nitrogen by passing a nitrogen stream through the separable flask. Next, the internal temperature was raised to 60°C, and 0.15 parts by mass of potassium persulfate and 5 parts by mass of deionized water were added. After that, the mixture was heated and stirred for 2 hours to terminate the polymerization, and an acrylic resin latex was obtained. The obtained acrylic resin latex was cooled to 25°C, then dropped into 500 parts by mass of 70°C warm water containing 5 parts by mass of calcium acetate, and then heated to 90°C to cause coagulation. The obtained coagulated product was separated and washed, and then dried at 60°C for 12 hours to obtain acrylic resin (C-1).
[0052] The amounts of various raw materials used in Example (C-1) were adjusted, and various acrylic resins C-2, C-3, and C-4 shown in Table 1 were obtained under the same production conditions as above.
[0053] [Table 1]
[0054] (D-1) Styrene-(meth)acrylic acid copolymer manufactured by Toyo Styrene Co., Ltd. (melt mass flow rate 1.7 g / 10 min, Charpy impact strength 1.5 kJ / m2, Vicat softening temperature 110°C, content of methacrylic acid monomer units 4% by mass) (D-2) Styrene-(meth)acrylic acid copolymer manufactured by Toyo Styrene Co., Ltd. (melt mass flow rate 1.7 g / 10 min, Charpy impact strength 1.1 kJ / m2, Vicat softening temperature 117°C, content of methacrylic acid monomer units 8% by mass) (D-3) Styrene-(meth)acrylic acid copolymer manufactured by Toyo Styrene Co., Ltd. (melt mass flow rate 1.8 g / 10 min, Charpy impact strength 1.0 kJ / m2, Vicat softening temperature 122°C, content of methacrylic acid monomer unit 10% by mass)
[0055] (E-1) Polycarbodiimide LA-1 manufactured by Nisshinbo (F-1) Oxazoline group-containing polymer RPS1005 manufactured by Nippon Shokubai (G-1) Epoxidized soybean oil NOF N-510
[0056] (H-1) Production of styrene-methyl methacrylate copolymer (content of methyl methacrylate monomer unit: 4% by mass) A monomer composition consisting of 4 parts by mass of methyl methacrylate as a monomer, 96 parts by mass of styrene, and 0.001 parts by mass of t-amylperoxy-2-ethylhexanoate (manufactured by Arkema Yoshitomi, product name: Luperox 575) as a polymerization initiator was continuously fed at 1 kg / h to a 10 L complete mixing tank equipped with a helical ribbon blade, and continuous polymerization was carried out at an average residence time of 2.5 hours and a polymerization temperature of 150° C. The liquid was continuously withdrawn from the bottom so that the liquid level in the polymerization tank was constant, and introduced into a desolvation device to obtain a pellet-shaped styrene-methyl methacrylate copolymer (H-1).
[0057] [Method of measuring reduced viscosity (ηsp / C)] The reduced viscosity (ηsp / C) of (A) styrene resin was measured by adding a mixed solvent of 17.5 ml of methyl ethyl ketone and 17.5 ml of acetone to 1 g of (A) styrene resin, shaking and dissolving for 2 hours at 25°C, then centrifuging to precipitate the insoluble matter, decanting to remove the supernatant, adding 250 ml of methanol to precipitate the resin matter, and filtering and drying the insoluble matter. The resin matter obtained by the same operation was dissolved in toluene to prepare a sample solution with a polymer concentration of 0.4% (mass / volume). The solution flow time in seconds for this sample solution and pure toluene was measured at a constant temperature of 30°C using an Ubbelohde viscometer, and the calculation was performed using the following formula. ηsp / C=(t1 / t0-1) / C t0: Pure toluene flow time in seconds t1: sample solution flow time in seconds C: Polymer concentration
[0058] [Method for measuring rubber polymer content] The rubber-like polymer content was measured by dissolving the rubber-modified styrene resin in chloroform, adding a certain amount of iodine monochloride / glacial acetic acid solution, and leaving the solution in a dark place for about 30 minutes. Then, 15% by mass potassium iodide solution and 50 ml of pure water were added, and the excess iodine monochloride was titrated with 0.1 N sodium thiosulfate solution, and the rubber-like polymer content was calculated from the amount of iodine monochloride added.
[0059] [Charpy impact strength measurement method] The Charpy impact strength was measured according to the ISO179 / 1eA method in accordance with JIS K7111.
[0060] [Method of measuring Vicat softening temperature] Test pieces were prepared using an injection molding machine and measurements were performed under conditions of a 50N load based on JIS K7206.
[0061] [How to prepare test pieces for evaluating constant strain chemical resistance tests] The pellets obtained in the extrusion process were dried by heating at 70°C for 3 hours, and then a sheet (width 200 mm x depth 300 mm x thickness 0.5 mm) was produced using a sheet extruder. Test pieces with the following dimensions were cut out from the produced sheet to be used as test pieces for evaluating the constant strain chemical resistance test. Sheet extrusion machine: Union Plastic USV type 30mm extrusion machine Cylinder temperature: 215℃ Roll temperature: 85℃ Test piece dimensions: Width 15 mm x Depth 150 mm x Thickness 0.5 mm (depth direction is the sheet extrusion direction)
[0062] [Evaluation method for constant strain chemical resistance test] The time to break according to the constant strain chemical resistance test method of the present invention was measured by applying 0.05 ml of a chemical with a dropper to the bent part of the test piece with gauze applied using a constant strain chemical resistance test device shown in the figure, measuring the time until the test piece broke, and determining whether the chemical resistance was acceptable or not according to the following criteria. Distortion: 0.6% Chemicals used: NOF Corp.'s Panacet 810 (medium-chain fatty acid oil) ◎: No breakage for 60 minutes or more. ×: Breaks within 60 minutes.
[0063] [Method for measuring weight average molecular weight] The weight average molecular weight (Mw) was measured by gel permeation chromatography (GPC) under the following conditions. GPC model: Showa Denko Co., Ltd. Shodex GPC-101 Column: Polymer Laboratories PLgel 10μm MIXED-C Mobile phase: Chloroform Sample concentration: 0.2% by mass Temperature: Oven 40℃ Detector: Differential refractometer In the present invention, the molecular weight of each component is measured at each elution time from the elution curve of monodisperse polystyrene. The molecular weight was calculated at 1000 g / mol and converted into polystyrene equivalent molecular weight.
[0064] [Method for measuring D-form content in polylactic acid resin] 0.3 g of polylactic acid was weighed out, added to 6 mL of 1N potassium hydroxide / methanol solution, and thoroughly stirred at 65°C. Then, 450 μL of sulfuric acid was added, and stirred at 65°C to decompose the polylactic acid, and 5 mL was measured as a sample. This sample was mixed with 3 mL of pure water and 13 mL of methylene chloride and shaken. After standing and separating, about 1.5 mL of the lower organic layer was collected, filtered with a 0.45 μm pore size HPLC disk filter, and then measured by gas chromatography using a Hewlet Packard HP-6890 Series GC system. The ratio (%) of the peak area of D-lactic acid methyl ester to the total peak area of lactate methyl ester was calculated, and this was taken as the D-form content (mol%) of the polylactic acid resin.
[0065] [Method for measuring lactide content in polylactic acid] 250 mg of polylactic acid was dissolved in 25 ml of diphenyl ether (DPE), and 3 ml of dichloromethane was added to completely dissolve the sample. Then, N-hexane was added to the solution to make a constant volume, and about 1.5 mL of the supernatant was collected. After filtering with a 0.45 μm pore size HPLC disk filter, the lactide content of polylactic acid was measured using a gas chromatograph. Gas chromatograph: GC-2014 (Shimadzu Corporation) Column: SUPELCO SPB-5
[0066] [Melt mass-flow rate measurement method] The strength was determined based on JIS K7210 under conditions of 200°C and a load of 49N.
[0067] [Method for measuring methyl methacrylate unit content] The content of methyl methacrylate units in the acrylic resin was measured as shown below based on the analytical method of Example 7 of JP-A No. 2001-141725.
[0068] 0.1023g of acrylic resin and 3.4613g of ethanol were charged into an autoclave (SUS316, internal volume 9ml, with pressure gauge) and the reaction was started by heating to 300°C in a sand bath. After 60 minutes, the autoclave was rapidly cooled, and after returning to room temperature, the reaction liquid was removed from the autoclave. The reaction liquid was filtered and the volume was adjusted to 10ml with ethanol. The alcohol obtained as the product was detected using a Hewlett-Packard gas chromatograph "HP5890" equipped with a J&W Scientific "DB-WAX" type column and an FID detector. The detected alcohol was quantified using the calibration curve method, and the content of methyl methacrylate monomer was calculated.
[0069] Next, a method for mixing the resin composition of the present invention will be described. Examples 1 to 11, Comparative Examples 1 to 10 (Example 7 is a reference example) (A) styrene-based resin, (B) polyester-based resin, (C) acrylic resin, (D) polymer containing a structural unit having a carboxyl group, (E) polycarbodiimide, (F) oxazoline group-containing polymer, (G) epoxidized soybean oil, and (H) styrene-methyl methacrylate copolymer were premixed in the amounts shown in Tables 2 and 3 using a Henschel mixer (Mitsui Miike Chemical Co., Ltd., FM20B), fed into a twin-screw extruder (Toshiba Machine Co., Ltd., TEM26SS) and formed into strands at a cylinder temperature of 200°C and a feed rate of 30 kg / h. The strands were then cooled with water and fed into a pelletizer to form pellets.
[0070] [Table 2]
[0071] [Table 3]
[0072] It is understood from the Examples in Table 2 that the resin composition of the present invention is excellent in chemical resistance, heat resistance and impact resistance, and from the Comparative Examples in Table 3 that the resin composition not satisfying the provisions of the present invention is inferior in chemical resistance, heat resistance or impact resistance.
Claims
1. A styrene-based resin composition comprising: (A) 30 to 80 parts by mass of a styrene-based resin; (B) 20 to 70 parts by mass of a polyester-based resin; (C) an acrylic resin; and (D) a polymer, The total amount of the styrene-based resin (A) and the polyester-based resin (B) is 100 parts by mass, The content of the (C) acrylic resin is 0.1 parts by mass to 10 parts by mass per 100 parts by mass of the total of the (A) styrene-based resin and the (B) polyester-based resin, the content of the polymer (D) is 1 part by mass to 35 parts by mass per 100 parts by mass of the total of the styrene-based resin (A) and the polyester-based resin (B), (D) the polymer is a styrene-(meth)acrylic acid copolymer; (A) the styrene-based resin is a rubber-modified polystyrene; (C) A styrene-based resin composition in which the structural unit of the acrylic resin is mainly a (meth)acrylate unit.
2. 2. The styrene-based resin composition according to claim 1, wherein the polyester-based resin (B) is polylactic acid.
3. 3. The styrene-based resin composition according to claim 1, wherein the weight-average molecular weight of the acrylic resin (C) is 1.5 million to 6 million.
4. 4. The styrene-based resin composition according to claim 1, wherein the structural unit of the acrylic resin (C) is mainly composed of methyl methacrylate units, and the content thereof is 60 mass % or more.
5. 5. The styrene-based resin composition according to claim 1, wherein the content of the structural unit having a carboxyl group in the polymer (D) is 0.5 to 9.5 mass %.
6. A sheet comprising at least one resin composition layer containing the styrene-based resin composition according to any one of claims 1 to 5 as a main component.
7. A food packaging container formed from the sheet according to claim 6.
Citation Information
Patent Citations
Impact-resistant polyester blend
JP1990281065A
Resin composition comprising styrene resin and polylactic acid
JP2008050427A
Resin composition and molding comprising the same
JP2008222790A
Lactic acid-acryl-styrene-based resin foam and lactic acud-acryl-styrene-based resin foam molding
JP2012201818A
Thermoplastic resin composition and molded article thereof
JP2013181046A